The role of advance rate in mining-induced stress and microseismic behavior during longwall face advance - Jiaxin Zhuang; Zonglong Mu; Piotr Małkowski; Wu Cai; Siyuan Gong; Anye Cao; Junjie Bai; Jinglong Cao (Geomatics, Natural Hazards & Risk)
Coal bursts are one of the most severe hazards in coal mining, yet the mechanisms linking advance rate, stress redistribution, and coal burst risks remain unclear. This study investigates these mechanisms using the Universal Distinct Element Code (UDEC) under specific geological conditions and varying advance rates, with a new method to model the evolution of microseismic (MS) events. Results show that increasing the advance rate leads to a faster transfer of stress from the roof to the coal seam, causing a larger change in the direction of the maximum principal stress. Consequently, the range of high-stress zones expands, and the peak abutment stress increases. In the model, the MS events mainly show a W-shaped distribution, with 103 J events dominating during initial roof movement and 104 J events during large-scale movements. An optimal advance rate of 6 m/d is identified. Exceeding this rate, such as at 8 m/d, increases the risk of coal bursts due to higher abutment stress and frequent high-energy MS events. Hydraulic fracturing can help mitigate this risk by addressing these high-energy MS events and the peak static loads caused by rapid advance rates.